2007
DOI: 10.1097/mlg.0b013e31804f8141
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Efficacy of Sublingual Immunotherapy in Patients With Perennial Rhinitis

Abstract: We suggest 3 years of sublingual immunotherapy for patients with perennial allergic rhinitis who require immunotherapy and do not accept the subcutaneous route of allergen administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 14 publications
0
29
0
1
Order By: Relevance
“…Overall, the clinical results obtained in this study are in agreement with other reports concerning SLIT and SCIT. 6,9,10 For instance, the carry-over effect 1 year after discontinuation of SLIT has been confirmed in a large randomized trial. 19 Another trial with SLIT has shown that a coseasonal treatment given for 3 consecutive years progressively increases the magnitude of clinical benefit.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Overall, the clinical results obtained in this study are in agreement with other reports concerning SLIT and SCIT. 6,9,10 For instance, the carry-over effect 1 year after discontinuation of SLIT has been confirmed in a large randomized trial. 19 Another trial with SLIT has shown that a coseasonal treatment given for 3 consecutive years progressively increases the magnitude of clinical benefit.…”
Section: Discussionmentioning
confidence: 88%
“…One of the most important questions is the optimal duration of a SLIT course to maintain a long-lasting effect, if any, and the opportunity to repeat the vaccination once the effect has vanished. In recent years, the long-lasting effect has been demonstrated for SLIT, 9,10 and it is now also known that the duration of the effect is partially dependent on the duration of immunotherapy itself. Nonetheless, in the earliest years of the use of SLIT, those aspects were totally unknown, and experimental data were urgently needed.…”
mentioning
confidence: 97%
“…One prospective, open study involving 60 children for 10 years [63] and one randomized, double-blind study involving 137 patients for 3 years [64] demonstrated a long-lasting effect of SLIT after discontinuation (after 5 years and after 3 years, respectively). Recently, 3 years of grass pollen SLIT resulted in consistent clinical improvement, accompanied by immunologic changes that were sustained 1 year after treatment in a large-scale, randomized, double-blind, placebo-controlled trial [65].…”
Section: Additional Effectsmentioning
confidence: 97%
“…This was recently demonstrated also concerning SLIT. In a study on SLIT performed by a dust mite extract, 137 patients were divided in 2 groups, 67 receiving the treatment for 2 years and 70 receiving the treatment for 3 years; all patients were followed-up for 3 years after stopping SLIT, and a greater improvement of symptoms was found in patients treated for 3 years [25]. In a prospective open controlled study, patients monosensitized to mites were divided in 4 groups, 1 receiving only drug treatment and the other 3 receiving SLIT for 3, 4, or 5 years.…”
Section: Efficacy Of Sublingual Immunotherapymentioning
confidence: 99%